Islamic micro-banking model with a target market of ultra-micro enterprises (case study of BTPN Syariah) - Muhari, Syafaat; Nadratuzzaman Hosen, Muhamad; Djamaluddin Sanrego, Yulizar (Jurnal Paradigma Ekonomika, 2024)
This research differs from previous research, in that this is focused upon analyzing the performance of the BPTN Syariah (compliant with Islamic banking rules) Bank, which is a commercial financial institution (bank) fully committed to financing the poor of society (ultra-micro enterprises), which comprise its market segment. This financing segment, in the category of ultra-micro and small enterprises, is considered to be one of high risk for a bank, The aim of this research was to evaluate to just what extent the performance of the BTPN Syariah was focused upon the financing of the ultra-micro enterprise segment of the poor of society. Based upon the analysis of the Risk Profile, of Good Corporate Governance, of Earnings, and of Capital (RGEC), it may be concluded that the BTPN Syariah had a much better rating than those of other Islamic banks, with a low level of risk and a high level of profitability. This different performance was brought about by the BTPN Syariah being supported by representatives/agents who empower and guide customers (customer service officers), which had an impact upon the creation of social capital. This showed that customers in the ultra-micro enterprise segment were of low risk when financed, and that the widening of financial access for the poor of society was needed.